The Relationship of Mother's Characteristics With The Incident of Bleeding in the Trimester of Pregnancy for Pregnant Women in the Regional Public Health City of Tanjung Balai City - Pohan, Rostina Afrida; Tanjung, Meni Fuji Astuty; Siringoringo, Erlina Esther Rotua (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2024)
As for becoming common/ public target from this research is to know " Relation/Link  of Characteristic of  Ms. With Occurence of blood of  at pregnancy of first trimester at  pregnant mother. Desain of this Research use method of research of Correlation that is focus  at  effort to know relation/link  of  among/between  some research variable, to test relation/link  of tersebur  is  perhaps needed  by  hypothesizing and test of relevant statistic  Nursalam, 2007. Sampel  is some of population or proxy of existing population above. If amount of sampel more than 100 hence, sampel can be taken  by  among/between  10-15% or 20-25%. And if sampel less than 100 hence, entirety of  population is  obliged to be made  by  sampel. Because population less than 100, Hence entirety of population  in  making sampel amounting to 30 people. This shares elaborate about Result of Penilitian of  at Haemorrahage  of   at pregnancy of first trimester  at  pregnancy mother, what is  in  obtaining through data collecting by using questioner to 30 people of responder that is mother of pregnancy residing in  region work puskesmas labuhan rasoki of town padangsidimpuan. As for suggestion expected by  for pregnant mother in order to more bayak look for soybean cake of information of  about first kehaamilan trimester. And in expecting for institution of health of mengupanyakan of counselling method.